Transformasi Sifat Tekstur dan Bahan Organik Tanah Psamment oleh Makro Biochar: Change in the Texture and Soil Organic Matter of Psamment Induced by Macro Biochar - Putri, Elsa Lolita; Iswanriyanto, Agus; Utami, kartika (UIR Press, 2026)
Background: Psamment soils utilized for sustainable agriculture face constraints due to low nutrient and organic matter content, as well as poor physical properties such as high bulk density, low water retention, and inadequate soil structure. Biochar is known to improve soil physical and chemical properties, but the effect of its particle size on Psamment soil remains underexplored. Objective: This study aimed to investigate the effect of biochar particle size on the physical properties (texture) and organic matter content of Psamment soil. Methods: Biochar was produced at a pyrolysis temperature of 450–500°C and fractionated into four dry sieve sizes: 2–1 mm, 1–0.5 mm, 0.5–0.1 mm, and <0.1 mm. Each biochar size was applied at a rate of 5% (w/w) to soil pots containing Psamment soil, with a control treatment (no biochar). All treatments were replicated five times, resulting in 25 experimental units. The pots were incubated at room temperature for 21 days, with moisture maintained at field capacity. Soil texture (hydrometer method) and organic carbon (Walkley & Black method) were measured after incubation. Results: The application of biochar, particularly the 2–1 mm size fraction, increased soil organic carbon content and improved the texture balance of Psamment soil compared to the control. The 2–1 mm biochar exhibited the highest organic matter content. Smaller biochar particles (<0.5 mm) showed reduced effectiveness. The control soil (without biochar) had 94.35% sand, 1.86% clay, and 3.79% dust, while biochar treatments altered the fractions. Conclusions: Fractionating biochar into macro-sized particles (<2 mm), specifically the 2–1 mm size, effectively increases soil organic matter content and improves the texture of Psamment soil